Active Flux Based Finite Control Set Model Predictive Control of Synchronous Reluctance Motor Drives - Hadla, Hazem (2020)
This paper presents two new finite control set model predictive control (FCS-MPC) strategies for synchronous reluctance motor (SynRM) drives, using the active flux concept. Both control strategies guarantee a fast and independent control of the torque and active flux of the SynRM, in order to obtain a high performance drive. The first strategy relies on a more conventional implementation of a FCS-MPC algorithm, which requires some effort to tune the weighting factors used in the cost function. The second control approach corresponds to a simplification of the first one, and allows a reduction of the calculation time associated to the predictions stage of the algorithm and, at the same time, avoids the use of weighting factors in the cost function. This allows to simplify the implementation of the control system, obtaining the same dynamic performance as with the first strategy. Experimental and simulation results verify the validity and effectiveness of the two proposed control schemes for SynRM drives. Furthermore, a state-of-the-art control technique like direct torque control is also considered in the paper, for performance comparison purposes.